Influenza and pneumococcus vaccination rates in pediatric dialysis patients in Europe: recommendations vs reality A European Pediatric Dialysis Working Group and European Society for Pediatric Nephrology Dialysis Working Group study - Atikel, Yeşim Özdemir; Bakkaloğlu, Sevcan A; Paglialonga, Fabio; Stefanidis, Constantinos J; Askiti, Varvara; Vidal, Enrico; Ariceta, Gema; Melek, Engin; Verrina, Enrico; Printza, Nikoleta; Vondrak, Karel; Zurowska, Aleksandra; et al. (Turkish journal of medical sciences, 2021)
BACKGROUND/AIM: Children on dialysis are under increased risk of influenza and invasive pneumococcal disease. Although vaccination against these microorganisms are recommended in dialysis patients and despite the fact that these vaccines can reduce disease burden and rates of hospitalization due to infection, vaccination rates are below expected and desired. We aimed to evaluate influenza and pneumococcal vaccination and infection rates in European pediatric dialysis centers. MATERIALS AND METHODS: In 16 centers from 11 countries, 357 pediatric dialysis patients were evaluated retrospectively during 1 year of observation period between 01.01.2014 and 01.01.2015. RESULTS: In all centers, vaccination policy included immunization of dialysis patients with inactive influenza vaccine and pneumococcal conjugate vaccine (PCV). Fifty percent of the centers recommended pneumococcal polysaccharide vaccine following routine PCV series. A significantly higher pneumococcal vaccination rate (43.9%) was seen in peritoneal dialysis (PD) patients compared to those on hemodialysis (HD) (32.9%) (p = 0.035), while the rates for influenza were similar (42.4% and 46.1% respectively, p = 0.496). Among all dialysis patients, 2.2% (n = 8) developed pneumonia and 6.4% (n = 23) was infected by Influenza. Pneumococcic pneumonia rate was 5% for 140 patients who received antipneumococcal vaccine, while only one pneumonia episode was recorded out of 217 unvaccinated patients (p = 0.007). The influenza virus infection rates were similar for patients vaccinated and nonvaccinated (7 % and 6 %, respectively). CONCLUSIONS: Although influenza and pneumococcal vaccines are highly recommended in pediatric dialysis patients, vaccination rates were lower than expected. Pneumococcal vaccination rates were higher in PD compared to the patients on HD. The rate of children with influenza infection was higher than pneumonia. The efficacy of influenza and pneumococcal vaccines was highlighted by the low infection rates. Higher pneumonia rates in patients vaccinated against pneumococcus compared to unvaccinated ones might be due to coexisting risk factors.
Keywords: Vaccination; Infant; Adolescent; chronická renální insuficience; nefrologie; Nephrology; Influenza Vaccines; pediatrie; dialýza ledvin; lidé; vakcíny proti chřipce; Antibodies; Retrospective Studies; Societies, Medical; společnosti lékařské; Humans; Influenza, Human; Child; retrospektivní studie; accination; Child, Preschool; Renal Dialysis; Dialysis; protilátky; imunizace; Streptococcus pneumoniae; pneumococcal vaccine; influenza vaccine; pneumokokové vakcíny; Immunization; kojenec; dítě; Pneumococcal Vaccines; chřipka lidská; mladiství; Renal Insufficiency, Chronic; immunization; vakcinace; Pediatrics; předškolní dítě